Growth Intention dan Pertumbuhan Pendapatan di UKM Sektor Keuangan : Peran Mediasi Pertumbuhan Ukuran Perusahaan (Studi Empiris pada Bank Perkreditan Rakyat Kota Malang yang Terdaftar di OJK Tahun 2017 - 2022) - Chofifa, Annisa Noor; Maslichah, Maslichah; Afifudin, Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to determine the effect of growth intention on revenue growth with company size growth as a mediating variable. The type of research used in this research is explanatory research. Meanwhile, the sampling method used was the purposive sampling method. The object of this research uses the Rural Bank (BPR) of Malang City which is registered with the Financial Services Authority (OJK) in 2017-2022. Of the 9 existing companies, there were 7 companies that met the sampling criteria in this research. The data analysis method used is path analysis assisted by SmartPLS v 3.2.9 software. The results of this test show that the relationship between growth intention has no influence on revenue growth, the relationship between growth intention and company size growth is significantly positive, the relationship between company size growth and revenue growth is significantly positive and company size growth mediates the effect of growth intention on revenue growth.Keywords: Growth intention, company size growth and revenue growth